PENGARUH ARUS KAS OPERASI, LABA AKUNTANSI DAN RETURN ON ASSET TERHADAP RETURN SAHAM - Harry Budiantoro; Hestin Agus Tantri Ningsih; Shabrina Alma; Kanaya Lapae (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine the effect of operating cash flow, accounting profit and return on assets on stock returns. The sampling technique used purposive sampling with a sample of 28 LQ-45 companies listed on the IDX in 2016-2019. This study uses secondary data, namely the company's financial statements obtained from the official website of the Indonesian Stock Exchange (IDX). The analytical method used s multiple linear regression. The results showed that accounting profit had a positive effect on stock returns. Operating cash flow and return on assets have no effect on stock returns..